HUBUNGAN KARATERISTIK RESPONDEN DENGAN TINGKAT KECEMASAN PETUGAS REKAM MEDIS PADA MASA PANDEMI COVID-19 DI RSUD WONOSARI - Anas Rahmad Hidayat (Jurnal Permata Indonesia, 2021)
ABSTRACT The corona virus (covid-19) entered Indonesia on March 2, 2019, where on that day there were two cases of positive COVID-19 patients. In general, the Covid-19 virus entered Indonesia by the government until now, Covid-19 has experienced a significant increase, health workers are included in the group that is vulnerable to being exposed to Covid-19 because health workers are in direct contact with patients. Keyword: Anxiety level, Covid-19 Pandemic